Cochrane systematic review and meta‐analysis of the impact of psychological treatments for people with epilepsy on health‐related quality of life. (3rd January 2018) - Michaelis, Rosa; Tang, Venus; Wagner, Janelle L.; Modi, Avani C.; LaFrance, W. Curt; Goldstein, Laura H.; Lundgren, Tobias; Reuber, Markus
Summary: Objective: Given the significant impact epilepsy can have on health‐related quality of life (HRQoL) of individuals with this condition and their families, there is great clinical interest in evidence‐based psychological treatments aimed at enhancing well‐being in people with epilepsy (PWE). An evaluation of the current evidence is needed to assess the effects of psychological treatments for PWE on HRQoL outcomes to inform future therapeutic recommendations and research designs. Methods: The operational definition of psychological treatments included a broad range of interventions that use psychological or behavioral techniques designed to improve HRQoL, psychiatric comorbidities, and seizure frequency and severity for adults and children with epilepsy. A systematic literature search was conducted in line with Cochrane criteria for randomized controlled trials (RCTs) and quasi‐RCTs investigating psychological treatments and using HRQoL outcome measures as primary or secondary outcome measures. Standard methodological procedures required by the Cochrane Collaboration were used for data collection and analysis. Results: Twenty‐four completed RCTs were included in this review (2439 participants). Based on satisfactory methodological homogeneity, data from 9 studies (468 participants) providing Quality of Life in Epilepsy‐31 (QOLIE‐31) outcomes were pooled for meta‐analyses, showing significant mean changes for QOLIE‐31 total score and 6 subscales. The significant mean changes of QOLIE‐31 total score (mean improvement of 5.68 points; 95% confidence interval = 3.11‐8.24, P < .0001) and 3 subscales (emotional well‐being, energy/fatigue, overall quality of life [QoL]) exceeded the threshold of minimally important change, indicating a clinically meaningful postintervention improvement of QoL. Overall, the meta‐analysis quality of evidence was characterized as "moderate" due to the risk of bias present in 8 of the 9 included studies (Handbook for Systematic Reviews of Interventions, Version 5.1.0, 2011, Chapters 8 and 12). A narrative synthesis was conducted for all trials and outcomes that were not entered in the meta‐analysis. Significance: These results provide moderate‐quality evidence that psychological treatments for adults with epilepsy may enhance HRQoL in people with epilepsy.